Enhanced catalytic performance for volatile organic compound oxidation over in-situ growth of MnOx on Co3O4 nanowire. (April 2020) - Zhao, Qian; Liu, Qingling; Zheng, Yanfei; Han, Rui; Song, Chunfeng; Ji, Na; Ma, Degang
Abstract: Hierarchical Co3 O4 @MnOx material has been synthesized by in-suit growth of MnOx on the Co3 O4 and applied in catalytic oxidation of volatile organic compounds (VOCs). Results revealed that T90 of acetone on the Co3 O4 @MnOx was 195 °C, which was 36 °C and 32 °C lower than that on the Co3 O4 and MnOx/Co3 O4, respectively. The universality experiments demonstrated that T90 of ethyl acetate and toluene on the Co3 O4 @MnOx were 200 °C and 222 °C, respectively. The above results indicated that Co3 O4 @MnOx catalyst presented a robust catalytic performance. Characterization results showed that high catalytic activity of the Co3 O4 @MnOx catalyst could be attributed to the improvement of low temperature reducibility, the enhancement of Co 3+ and adsorbed oxygen species resulted from the sufficient reaction between MnO4 − and Co 2+ during secondary hydrothermal process. Furthermore, stability and water-resistance experiments showed the Co3 O4 @MnOx catalyst with high cycle and long-term stability, satisfied endurability to 5.5–10 vol. % water vapor at 210 °C. Graphical abstract: Image 1 Highlights: Co3 O4 @MnOx exhibits an outstanding performance for VOC oxidation. Plentiful Co 3+ species are formed on the Co3 O4 @MnOx by the redox reaction between MnO4 − and Co 2+ . Co 3+ species are the main active sites of Co3 O4 @MnOx for VOC oxidation.